Coding-Decoding Protocol-Based Data-Driven Adaptive Sliding Mode Control Under Energy-Constrained DoS Attacks - Chang, Lina; Chi, Ronghu; Hou, Zhongsheng (IEEE transactions on automation science and engineering, 2025)
The security tracking control problem is addressed for nonlinear discrete-time networked control systems (NCSs) subject to energy-constrained denial-of-service (EC-DoS) attacks. A probabilistic quantization-based coding-decoding protocol (CDP) is designed to mitigate bandwidth limitations and enhance transmission security. Then, a CDP-based data-driven adaptive sliding mode control (DDASMC) method is presented on the basis of a linear data model (LDM) of the nonlinear NCSs. A detection algorithm is designed to detect EC-DoS attacks so that the proposed CDP-based DDASMC can automatically switch between two cases with and without EC-DoS attacks, respectively. In the duration that the attack does not occur, an integral sliding function and a reaching law are designed to achieve fast convergence while ensuring a good control performance. In the duration that the attack occurs, a prediction mechanism is introduced to construct a predictive LDM for estimating future control information. Further, a sliding mode predictive control is developed to address the EC-DoS attacks and enhance the control performance. All the algorithms of the proposed DDASMC are computed only using the input-output (I/O) data instead of any other information of the physical models. Simulation study validate the results. Note to Practitioners-NCSs have been extensively applied in numerous fields, such as smart grid and aerospace. However, the open network environment provides attackers with many opportunities for cyber-attacks, resulting in the deterioration of control performance. Accordingly, it is urgent to analyze the security problems of NCSs that are vulnerable to cyber-attacks. This study considers the security tracking control problem of NCSs under EC-DoS attacks. A probabilistic quantization-based CDP is introduced for the feedback channel to reduce the bandwidth of communication networks and improve the security of data transmission by compressing the data before transmission. Then, a detection mechanism is proposed to determine whether NCSs are attacked, and a DDASMC with a switching mechanism is developed to address both cases with and without EC-DoS attacks. The presented control method is data-driven and includes an adaptive switching mechanism that not only saves resources but is also more suitable for practical applications.